Estudio del perfil académico y biopsicológico de estudiantes que ingresan a las carreras de grado de la ESPAM MFL, abril 2018/marzo-2019 - Montesdeoca Zambrano, María Victoria (2019)
The objective of this research was to determine the academic and bipsychological profile of students entering the undergraduate degrees of Escuela Superior Politécnica Agropecuaria de Manabí Manuel Félix López, April – 2018 / March-2019. The methodology used was the field and documentary research through the instruments of the interview and survey, information collection, tabulation and analysis were facilitated too; the survey was applied to a total of 821 students and the interview to the eight career directors: Agribusiness, Veterinary Medicine, Environmental Engineering, Agricultural Engineering, Tourism, Computing, Business Administration and Public Administration. The statistical software SPSS (Statistical Package for the Social Sciences) in version 25 was used to process quantitative data, in addition to the help of deductive, inductive and analytical-synthetic methods, an exhaustive analysis of academic and biopsychological factors was achieved. that have an impact on students' personal and professional training, an improvement plan was subsequently designed with support and accompaniment strategies that contribute to improving the retention rate, reducing attrition and increasing the degree rate.